Twenty four-month follow-up after bullectomy, unilateral and bilateral lung volume reduction surgery: a single-center retrospective analysis of consecutive cases - Slavisa Bascarevic; Maja Ercegovac; Mir Alireza Hoda; Milan Savic; Radomir Vesovic; Vladimir Milenkovic; Marina Moromila; Marko Popovic; Daniela Gompelmann; Petar Madzarevic (European Journal of Medical Research, 2024)
Abstract Purpose While pharmacologic therapy remains the cornerstone of lung emphysema treatment, surgery is an additional therapeutic option in selected patient groups with advanced emphysema. The aim of lung volume reduction surgery (LVRS) is to improve lung function, exercise capacity, quality of life and survival. We sought to determine the therapeutic value of surgical resection in specific patients with lung emphysema. Patients and methods A retrospective study was performed consisting of 58 patients with lung emphysema who underwent surgical intervention over a 10-year period and were followed for 2 years postoperatively. The clinical characteristics recorded were FEV1 (forced expiratory volume in 1 s), the 6-min walk test (6-MWT), the Modified Medical Research Council (mMRC), body mass index (BMI) and quality of life prior to and 6, 12 and 24 months after surgical intervention. Moreover, all peri- and post-operative complications were noted. Results Out of 58 emphysema patients (72% male, FEV1 (L) 2.21 ± 0.17, RV (L) 3.39 ± 0.55), 19 underwent surgical bullectomy, 31 unilateral LVRS and 8 sequential bilateral LVRS. Six months after surgery, there was a statistically significant improvement in FEV1, RV, TLC, 6-MWT and mMRC. Over a period of 12 to 24 months postoperatively, clinical benefit gradually declines most likely due to COPD progression but patients still experienced a significant improvement in FEV1. The most common postoperative complications were persistent air leakage (> 7 days), arrhythmia and subcutaneous emphysema in 60%, 51.6% and 22.4%, respectively. No deaths were observed after surgical intervention. Conclusion In a selected patient population, surgery led to significant improvement of lung function parameters, exercise capacity and quality of life. Over a period of 12 to 24 months postoperatively, clinical benefit gradually decreased most likely due to COPD progression.